Особливості розподілу швидкостей поширення сейсмічних хвиль у земній корі Кіровоградського рудного району - Трипільський, О.А.; Трипільська, О.А.; Тополюк, О.В. (Геофизический журнал, 2015)
Показана принципиальная возможность детального исследования скоростных характеристик кристаллической земной коры в местах расположения месторождений урана. На основании сопоставления с геологическими данными высказано предположение о повышенной концентрации натровых метасоматитов и урановых руд на глубине 0-4 км. Установлены сложные соотношения между скоростями в земной коре месторождений урана и на участках вне их, что свидетельствует об особом распределении скоростей в земной коре месторождений урана. Principal possibility of detailed study of velocity characteristics of crystalline Earth's crust in the areas of uranium deposits has been shown. By comparison with geologic data an assumption has been expressed on increased concentration of sodium metasomatites and uranium ores at a depth of 0-4 km. Complicated correlations have been revealed between the velocities in the Earth's crust of uranium deposits and in the areas outside them that is an evidence of special fea-tures of velocity distribution in the Earth's crust of uranium deposits.